IMPROVING THE METHOD OF TRAINING BOXERS WITH THE APPLICATION OF PROTECTION "LEAVING TO THE SIDE" (World Bulletin of Management and Law, 2022)
Training a boxer in both stances with side steps leads to symmetry, which ensures better results. The advantage of a boxer who has mastered steps to the side and boxing in both stances is considered.